Analysis of Compensation Mechanisms as Business Actor Liability for Overclaim in Azarine Skincare Products - Sinaga, Guna Gerhat; Surahmad (Journal of Law, Politic and Humanities, 2025)
The purpose of this paper is to analyze the compensation mechanism as a form of business actor's accountability for overclaim practices in skincare product promotions, focusing on a case study of the Azarine product. Overclaim is an action by business actors in providing excessive information or claims regarding the benefits of a product without adequate scientific evidence. This practice not only violates the principles of transparency and honesty in promotion but also has the potential to mislead and harm consumers. This study uses an empirical legal method with a statutory approach and a case approach. The results of the study show that overclaims carried out by business actors violate the provisions of Law Number 8 of 1999 concerning Consumer Protection and BPOM Regulation Number 3 of 2022 concerning Cosmetic Claims. Business actors who are proven to have committed overclaims are obliged to be responsible for providing compensation to consumers in the form of a refund, product exchange, or other compensation in accordance with the losses experienced. This shows the importance of business actors' responsibility to ensure that consumer rights are fulfilled